Economic Resilience and Crime: A Phenomenological Study of Public Perceptions on the Weakening of the Local Economy on Criminal Behavior - Widiatmoko, Dekki; Khoirunnisa, Khoirunnisa; Jubaidi, Didi; Akib, Syubhan; Saputra, Dedi; Efendi, Sofian; Habibah, Habibah; Ningsih, Wahyu (The Republic of Indonesia Defense University, 2024)
The weakening of the regional economy is often a complex social problem. Criminal behavior can occur such as theft of residents' houses caused by the weakening of the regional economy. The study was conducted in Merangin Regency, Jambi Province, which is the second largest palm oil producing province after Riau Province. Merangin is a district with the largest palm oil productivity in Jambi Province. Merangin Regency's dependence on palm oil production is the reason why this location is suitable for research. This study is included in qualitative research with a phenomenological approach that examines precisely and in depth the influence of the regional economy on criminal theft behavior in Merangin Regency, Jambi Province. The weakening of the regional economy due to dependence on income from the weakening of palm oil production and fluctuations in the price of determining Fresh Fruit Bunches (FFB) which have an impact on criminal behavior such as theft. This is caused by the loss of people's fixed income and the influence of other factors such as drug consumption which requires perpetrators to fulfill their needs by stealing. The weakening of the local economy also causes low microeconomic resilience because the fulfillment of household needs is reduced and income is also reduced. Meanwhile, national security, which is a function of the police institution, is also disrupted because negative assumptions about the police are developing in society, resulting in feelings of reluctance and fear of reporting to the police if a criminal act of theft occurs in Merangin Regency.